2001
DOI: 10.1080/09500830110088755
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the g · b x u = 0 edge dislocation invisibility criterion for electron channelling contrast imaging

Abstract: Dislocations with a large edge component do not exhibit a full loss of di raction contrast in the transmission electron microscope unless the conditions g· bˆ0 and g· b uˆ0 are simultaneously met. Because of a similarity between transmission electron microscopy (TEM) di raction contrast and electron channelling contrast in the scanning electron microscope, the same contrast rules would be expected to apply for electron channelling contrast imaging (ECCI). Using the characteristic edge dislocations formed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 11 publications
(3 reference statements)
0
38
1
Order By: Relevance
“…While both the g b ¼ 0 (Morin et al, 1979;Czernuszka et al, 1990b;Simkin and Crimp, 1999) and the g b 3 u ¼ 0 (Crimp et al, 2001) invisibility criteria have been demonstrated for ECCI, in practice, significant care must be taken when interpreting such contract analysis. TEM allows reasonable images of dislocations to be obtained for a significant range of positive deviations from the Bragg condition (Hirsch et al, 1965).…”
Section: Ecci Contrast Analysis and Limitationsmentioning
confidence: 98%
“…While both the g b ¼ 0 (Morin et al, 1979;Czernuszka et al, 1990b;Simkin and Crimp, 1999) and the g b 3 u ¼ 0 (Crimp et al, 2001) invisibility criteria have been demonstrated for ECCI, in practice, significant care must be taken when interpreting such contract analysis. TEM allows reasonable images of dislocations to be obtained for a significant range of positive deviations from the Bragg condition (Hirsch et al, 1965).…”
Section: Ecci Contrast Analysis and Limitationsmentioning
confidence: 98%
“…While many of these studies implement ECCI to observe dislocations, only one study on FeAl single crystals has demonstrated an invisibility criterion via channeling contrast to characterize individual dislocations. 13 This capacity could uniquely be applied to correlate defect behavior for both substrates and overlying epitaxial films since ECCI could be conducted pre and post growth.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, defined diffraction conditions based on ECP [14,22,43,44] or SACP [45,46] were necessary for the investigation of individual dislocations by ECCI. However, these methods are limited by necessary large grain sizes (ECP) or instrumental conditions (SACP) [50] is used to calculate diffraction patterns of studied ECCI areas.…”
Section: Combination Of Ecci With Other Sem Techniquesmentioning
confidence: 99%